Report on 13th Polish Conference in “Humanistic Ecology” Series: “Nature as a Challenge for Culture. Local Communities Towards Protected Areas” (Warsaw 16-17 October 2019) - Sadowski, Ryszard F. (Studia Ecologiae et Bioethicae, 2020)
The summary is not available.